Soil Test Technology for Developing Fertilizer Recommendations of Lowland Rice - Al-Jabri, Muhammad (+622518321746, 2013)
Soil test technology is an invaluable tool in determining the availability of soil nutrient status accurately in accordance with plant requirement. Application of inorganic fertilizer continuously at a rate that exceeds the plant needs can lead to nutrient imbalance due to the decreasing soil pH and accumulation of P and K in the soil resulting in nutrient disorder. This problem can be solved by specific location nutrient management supported with soil test technology. Utilization of soil test technology in balanced fertilizer application needs to be supported by P and K nutrient status maps, soil test kit, and fertilizer recommendation software. In the future, development of soil test technology aimed to improve land productivity and fertilizer efficiency by improving site-specific balanced fertilizer application integratedly with inorganic and organic fertilizers and other materials as soil conditioner. Strategies for developing soil test technology include: (1) replacing the original soil analysis method using a single nutrient soil analysis (SNSA) with multi-nutrient soil analysis (MNSA) and validating it in paddy soil in Indonesia; (2) validating and updating P and K nutrient status maps of 1:250,000 scale and 1:50,000 scale periodically; (3) developing soil test kit not only to measure P and K nutrient status, but also other nutrients such as N, S, Ca, and Mg; (4) establishing networks and linkages between soil testing laboratories and farmer groups in order to socialize balanced fertilizer recommendations; (5) improving the Regulation of the Minister of Agriculture No. 40/2007 regarding to the recom- mendation for N, P, and K fertilizer on rice to improve the accuracy of site-specific fertilizer recommendations; and (6) closing soil test technology to farmers as end-user to form an integrated ground test clinic (mobile soil test). This last strategy is to complement the achievement of good agricultural practices (GAP), which is associated with precision farming including the nature of the soil, plants, and site-specific fertilizer recommendations in exact rate, time, and application method.